Accountability of Children's Services Organizations in China. Issue 1 (February 2015) - Fisher, Karen R.; Shang, Xiaoyuan; Li, Jing
<x xml:space="preserve">Abstract</x> The accountability of children's services organizations is a current challenge in China as its social service system expands. The government is beginning to fund children's services organizations directly; however, the accountability practices remain weak. This has created a credibility crisis with the public about the use of donations and quality of services. Some organizations are starting to engage with their service users to address this problem. User participation is an important approach for China, since government regulation of nongovernment organizations is limited. This qualitative case study applies a multidimensional accountability framework (managerial and democratic) to examine participation practices in a child disability organization founded by parents. We found that the governance and operational structures attempted to provide accountability to all stakeholders, but top‐down accountability to government and donors was prioritized over accountability to children and families. Accountability for professional and technical quality was supported by international professional organizations, which is an option only available to some NGOs. Government support for multidimensional aspects of accountability needs to extend beyond funding, to training and technical support to achieve quality service provision by NGOs.